Managing University of Sharjah Setting and Infrastructure Towards a Sustainable and Livable Campus - Mushtaha, Emad; Alsyouf, Imad; Bettayeb, Maamar; Al Jaberi, Bushra Hussein; Al Mallahi, Maryam (Universitas Diponegoro, 2022)
This paper describes the setting and infrastructure management at the University of Sharjah (UoS) as a continuous effort towards a livable and sustainable campus. The UoS has been participating in the UI GreenMetric World Universities Ranking (UIGWUR) since 2017 to measure its performance in the field of sustainability for continuous improvement. During the last three years, the UoS has succeeded in being among the best 150 universities in the SI category by achieving 70% of the score. However, the UoS managed to get 75% of the total score in this KPI and 100% in the open space per person KPI ratio. To become one of the leading universities, the Landscape and Building Management Sustainability Circle (LBMSC) at the Sustainability Office has analyzed the KPIs and suggested an action plan for continuous improvement. Two KPIs can be improved: sustainability efforts and the total area covered in plants. The UoS shall increase the sustainability efforts and budget and increase the internal and external planting in the coming years. For some KPIs, it cannot be applied to desert regions. It is recommended that the UIGWUR revisit its KPIs and make them more flexible and applicable worldwide. Furthermore, for the open space ratio to the total area KPI, it is recommended to revisit the distribution of the points to have fair comparison. Action plans to improve the sustainability and livability of the campus have also been addressed.Keyword: Setting and infrastructure, LBMSC, livable campus, open area, forest, water absorption, green area, sustainability efforts/budget, and GreenMetric